Comparing Returns: Do Indonesian Government Bonds Underperform Mutual Funds and Stocks? - Irianto, Kurniawan Budi; Kamaludin, Kamaludin; Usman, Berto (Department of Management, Faculty of Economics and Business, Brawijaya University, 2025)
Investment has long been common among Indonesians, with gold traditionally favored. Recently, younger generations have begun diversifying into capital market instruments such as stocks, mutual funds, and Indonesian government bonds (ORI). While these options offer higher return potential, they also carry greater risk. Retail investors often face obstacles such as limited capital, time constraints, and lack of accessible information, which can hinder optimal investment decisions. This study compares the returns of stocks, mutual funds, and ORI from February 22, 2021, to February 15, 2024. A modified present value formula is used to evaluate each investment, incorporating all cash flows coupon payments, cash dividends, and stock dividends throughout the investment period. This approach addresses a common gap in investment prospectuses, where present value considerations are frequently omitted by investment managers, leading to less accurate return assessments. Findings show that, on average, stocks deliver the highest returns, followed by ORI, with mutual funds yielding the lowest. These results provide practical insights for retail investors aiming to make more informed decisions based on return potential adjusted for the timing of payments.